Analisis Penggunaan Filter Harmonic Untuk Mengurangi Efek Harmonisa Pada Sistem Kelistrikan Kapal Isap Produksi - Putra, Aseftian Wanda (ENERGI & KELISTRIKAN, 2023)
Harmonics are disturbances caused by non-linear loads, the negative impact of the presence of harmonics, among others, overheating of motors, transformers, capacitors and neutral wires as a result of the emergence of harmonics. This research was conducted so that the value of harmonics that exceeds the standard value can be reduced by using a filter to reduce the effects caused by harmonics on the ship's electrical system. Based on Load Flow Analysis, it can be seen several values ??in the form of active power of 60 kW, reactive power of 39 kVAR, apparent power of 72 kVA, power factor of 84% and current flowing in the network of 103.2 A. Standard harmonics used are 8%, Single Tuned Harmonic Filter, the capacitor capacitance value is 19.2 kVAR, the capacitor value is 381 F. The value of the inductor on the 3rd order with a harmonic value of 2.85 and the inductor 0.0032 H. The value of the inductor on the 5th order with a harmonic value of 4.75 and the inductor 0.0012 H. The value of the inductor on the 7th order with a harmonic value of 6.65 and the inductor 0 .0005 H and the results of the installation of a single tuned harmonic Filter on the R, S, and T phases on the three orders of 3, 4 and 5 obtained a THD value that meets the 8% harmonic standard, a Single Tuned Harmonic Filter of Order 5 is suitable for reducing harmonics on ships. Main Production because it meets harmonic standards in each phase.